COMPARISON OF ENAMEL SURFACE ROUGHNESS PARAMETERS FOR RESIN REMOVAL FOLLOWING DEBONDING USING TUNGSTEN CARBIDE BUR AND SOFLEX DISCS WITH HIGH SPEED AND LOW SPEED HAND PIECES - Saadia Nazir; Javeria Asif Cheema; Farhan Ahmed; Usman Qadir Khan; Muhammad Anwaar Alam; Syeda Tehmina Rehman (Pakistan Oral & Dental Journal, 2020)
This study was done to compare the enamel surface roughness parameters and the time taken to remove the resin from tooth surface after de-bonding, using tungsten carbide bur (TCB) and soflex discs with high and low speed hand pieces. It was a Randomized control trial, and was conducted at Children’s Hospital/Institute of Child Health and PCSIR, Lahore from 1st January 2016 to 31st December 2016. A total of 60 patients (30 in each group) were enrolled. Group A comprised of patients in which resin remnant was removed by TCB in high speed hand piece (HSHP) whereas in Group B, resin remnant was removed by TCB in low speed hand piece (LSHP) followed by soflex discs in both groups. Root mean square roughness (μm) changes were noted as 1.45±1.79 and 1.56±0.82 (μm) in Group A and B respectively. Maximum roughness depth (μm) changes were 4.36±2.93 in Group A and 4.33±3.92 (μm) in Group B. Time (sec) consumed in group A was 29.47±4.06 and in group B was 29.67±4.18. It was concluded that TCB in LSHP along with soflex disc produces slightly more roughness as compared to TCB in HSHP and soflex disc. However, the difference was not statistically significant. Slightly less time was taken by tungsten carbide bur and soflex disc in HSHP.
Keywords: Diamond bur; enamel surface roughness; tungsten carbide bur